1993
DOI: 10.1901/jeab.1993.59-115
|View full text |Cite
|
Sign up to set email alerts
|

Motion as a Natural Category for Pigeons: Generalization and a Feature‐positive Effect

Abstract: Three groups of pigeons were trained with a modified discriminative autoshaping procedure to discriminate video images of other pigeons on the basis of movement. Birds of all groups were shown the same video images of other pigeons, which were either moving or still. The group to whom food was presented only after moving images learned the discrimination very quickly. A second group, to whom food was given only after still images, and a pseudocategory group, to whom food was presented after arbitrarily chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 28 publications
3
62
2
Order By: Relevance
“…As such, could the pigeons have been simply seeing the videos as static displays? Dittrich and Lea (1993) found that pigeons can easily discriminate between static pictures and dynamic videos of similar content, so it is likely they were doing so here. Further, the reduced peck rates to the videos and the gradual improvement with experience each suggest that the videos were seen as fundamentally different from the static displays.…”
Section: Discussionmentioning
confidence: 89%
“…As such, could the pigeons have been simply seeing the videos as static displays? Dittrich and Lea (1993) found that pigeons can easily discriminate between static pictures and dynamic videos of similar content, so it is likely they were doing so here. Further, the reduced peck rates to the videos and the gradual improvement with experience each suggest that the videos were seen as fundamentally different from the static displays.…”
Section: Discussionmentioning
confidence: 89%
“…The discrimination eventually transferred fairly weil to the new stimuli in Test 2. Dittrich and Lea (1993) found that pigeons could respond discriminatively to moving and static video images ofobjects, including pigeons, humans, other animals, parts of a tree, and computer-generated geometrical shapes. They interpreted this as the formation ofa "motion" concept by pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…Labels facilitate shape recognition by calling attention to distinguishing features (Daniel & Ellis, 1972). If the distinguishing element is the presence of a feature, animals naturally learn to attend to it, and discriminations are swift and robust; if the distinguishing element is the absence of a feature, attention lacks focus, and discrimination is labored and fragile (Dittrich & Lea, 1993;Hearst, 1991), as are attend-toeverything strategies in general.…”
Section: Paths To the Logitmentioning
confidence: 99%